Design and development of a wireless indoor smart energy saving and monitoring - Koay, Li Woon (2019)
Smart Homes or Home Automation becomes famous and different new technology begins to emerge recently. A number of improvements make Smart Home better quality and marketed to the public. To allow the Smart Home system more reliable to any places, modification of an existing work building becomes an idea in the society especially in Malaysia. This research describes a system to convert a conventional into an intelligent working area. A Smart System is introduced to reserve energy. Nowadays, the trends show that highly demand electricity in the society. The issue of rapid energy losses has been discussed around the corner. Energy losses bring the impact of soaring prices of electricity and power production reduces. All the consumers have no idea about the reasons of energy losses. In this research, the design of a wireless and reliable indoor smart power saving system is to minimize the energy losses for the work stations area. Not only have that, the system is able to monitor and analyse the power consumption specialised in each of sections in work building. Modification of an existing work building is highly recommended compare to rebuild a building. The cost is lower if apply a system in existing building and brings out an equivalent standard compare to a new building. Some basic equipment which easily to get and purchased with a lower price to produce the system and apply in the work area, to minimize the cost using and maximize the energy saving. A variety of equipment are used include a programmable controller, transceiver module, relay switches, sensors and others to build up the system. The system will control the operation of electrical appliances in work building based on the conditions of offices. The system works also in fully automated and wireless. When there is someone in the office room, the system will turn ON the appliances immediately. However, when there is no one in the office after certain time, the system will turn OFF the appliances. On top of that, the system is portable to use in anywhere. This concept brings the conveniences and easily to save the energy in any work building. The Monitoring System plays a role to monitor the condition of every office room in work building. This monitoring concept is able to detect the occupancy of the staff in real time during working hours. This shows that the valuable and more advances compare to the technology already in market in this research. Moreover, the system will make data analysis according to the results collected in daily working hour. The data analysis will shows the different between before and after the system is applied in work area. From the comparison results, the application of Smart Energy Saving and Monitoring System is reliable to be placed in work area. The requirement to install the system is according to different locations, different identity of user and the period of using the system. Lastly, the results showed that the total energy used was reduced. For example, the total energy used in lecturer hall had reduced 18kWh. A higher percentage of total energy estimated saves up to 50% was showed after the system was applied. The results proved that the system is applicable and reliable to the user in work area. Thus, this system takes into account the architecture of human cognition and it is highly demand in market to achieve a lower energy usage at the same with high quality and comfortable life.